2017
DOI: 10.3390/ijms18071536
|View full text |Cite
|
Sign up to set email alerts
|

UV-Surface Treatment of Fungal Resistant Polyether Polyurethane Film-Induced Growth of Entomopathogenic Fungi

Abstract: Synthetic polymers are the cause of some major environmental impacts due to their low degradation rates. Polyurethanes (PU) are widely used synthetic polymers, and their growing use in industry has produced an increase in plastic waste. A commercial polyether-based thermoplastic PU with hydrolytic stability and fungus resistance was only attacked by an entomopathogenic fungus, Metarhiziumanisopliae, when the films were pre-treated with Ultraviolet (UV) irradiation in the presence of reactive atmospheres. Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Previous studies have shown the benefits of using AA vapors in plasma treatments to increase the PV performance of the membranes 31,32 and UV‐assisted treatments to induce biodegradation processes in polymers 34 . In those reports, for example, it was verified that a typical result of the UV‐assisted treatments in the presence of AA vapors on polymers was the polymerization of a poly(acrylic acid) (PAA) like film on top of the untreated film 43 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown the benefits of using AA vapors in plasma treatments to increase the PV performance of the membranes 31,32 and UV‐assisted treatments to induce biodegradation processes in polymers 34 . In those reports, for example, it was verified that a typical result of the UV‐assisted treatments in the presence of AA vapors on polymers was the polymerization of a poly(acrylic acid) (PAA) like film on top of the untreated film 43 .…”
Section: Resultsmentioning
confidence: 99%
“…VUV 36 and UV 34,37,43 irradiation was carried out following a methodology already published. Briefly, a Deuterium almost monochromatic source (162 nm) of 140 W (Hamamatsu, Japan) fitted in a homemade stainless steel photochemical reactor was used as a VUV source.…”
Section: Vuv and Uv-c Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations